Duties and Rights of Husband and Wife According to KH. Hasyim Asy’ari in the Book Dau’ Al-Misbah Gender Perspective - Basithul Arzaq, Farid Wajdi; Sukti, Surya; Norhadi, Muhammad (Journal of Law, Politic and Humanities, 2025)
This paper examines domestic partners who do not fully understand the obligations and rights of each husband and wife. This lack of understanding can lead to an imbalance in the relationship and the potential for conflict. The main focus is on the concept of Obligations and Rights of husband and wife according to KH. Hasyim Asy'ari in the book ?au' al-Mi?b?h and the relevance of the Obligations and Rights of husband and wife in the present. The research method used in this research is library research with a research approach using literature (library research) using a qualitative approach with a content analysis approach method. The result of the research on the obligations and rights of husbands and wives according to KH. Hasyim Asy'ari in the book ?au' Al-Mi?b?? from a gender perspective is that the Quran is very wise by mentioning that the relationship between husband and wife must be built in a mu'?syarah bi al-ma'rûf manner. A good husband is a husband who can please, take care of and help his wife just as his wife pleases him, takes care of him and helps him, and the husband must be patient with his wife's shortcomings and vice versa. The obligations and rights of husband and wife in Imam Malik's opinion are the suitability of maslahah which is seen as a stand-alone source of evidence with the purpose of shari'ah (al-maqasid al-shari'ah), maslahah must make sense (rationable), the use of this maslahah argument is in order to eliminate the difficulties that must occur. As long as the working wife does not forget the family, because by nature, the wife is still obliged to take care of the household and pay attention to the family.